The evolution of the role of ABA in the regulation of water-use efficiency: From biochemical mechanisms to stomatal conductance. (October 2016) - Negin, Boaz; Moshelion, Menachem
Highlights: ABA's regulation of guard cells yielded a wide variety of WUE-regulation mechanisms. ABA takes part in non-stomatal, biochemical mechanisms of WUE regulation. ABA appears to initiate leaf senescence, to directly inhibit photosynthesis. Cam plants day time stomatal closure may be caused by hypersensitivity to ABA. Abstract: Abscisic acid is found in a wide variety of organisms. In the plant kingdom, ABA's role in mediating responses to abiotic stress has been conserved and enhanced throughout evolution. The emergence of plants to terrestrial environments required the development of mechanisms to cope with ongoing and severe abiotic stress such as drought and rapid changes in humidity and temperature. The common understanding is that terrestrial plants evolved strategies ranging from desiccation-tolerance mechanisms (mosses) to drought tolerance (CAM plants), to better exploit different ecological niches. In between these divergent water regulation strategies, ABA plays a significant role in managing plants' adaptation to new environments by optimizing water-use efficiency (WUE) under particular environmental conditions. ABA plays some very different roles in the regulation of WUE. ABA's role in the regulation of guard cells and transpiration has yielded a wide variety of WUE-regulation mechanisms, ranging from no sensitivity (ferns) to low sensitivity (anisohydric behavior) to hypersensitivity to ABA (isohydric behavior and putatively CAM plants). ABA also plays a role in the regulation of non-stomatal, biochemical mechanisms of WUE regulation. In angiosperms, this includes the control of osmotic adjustment and morphological changes, including changes in leaf size, stomatal density, stomatal size and root development. Under severe stress, ABA also appears to initiate leaf senescence via transcriptional regulation, to directly inhibit photosynthesis.